2019
DOI: 10.1101/535609
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Genome-engineered Bioartificial Implant for Autoregulated Anti-Cytokine Drug Delivery

Abstract: Biologic drug therapies are effective treatments for autoimmune diseases such as rheumatoid arthritis (RA) but may cause significant unwanted adverse effects, as they are administered continuously at high doses that can suppress the immune system. As the severity of RA fluctuates over time, targeted strategies that can dynamically sense and respond to changing levels of endogenous inflammatory mediators may achieve similar therapeutic efficacy while reducing risks of adverse effects. Using CRISPR-Cas9 genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Furthermore, the development of genome editing techniques has led to the development of ‘designer cell’, including modification of receptors, gene networks or transgenes, laying the foundation for new cell therapies [ 20 ]. For example, it has shown that CRISPR-Cas9 engineered stem cells have a synthetic genetic circuit which can respond in an auto-regulated, feedback-controlled manner, and express biological drugs against interleukin-1 (IL-1) or tumor necrosis factor A (TNF-A) [ 69 ]. Inflammatory cytokines are the most important compounds involved in the pathogenesis of OA [ 70 ], and they imbalance the homeostasis of the joint tissue by promoting catabolic and destructive processes [ 71 ].…”
Section: Engineering Mscs Behavior Through Materials-mediated Gene Delivery and Gene Editingmentioning
confidence: 99%
“…Furthermore, the development of genome editing techniques has led to the development of ‘designer cell’, including modification of receptors, gene networks or transgenes, laying the foundation for new cell therapies [ 20 ]. For example, it has shown that CRISPR-Cas9 engineered stem cells have a synthetic genetic circuit which can respond in an auto-regulated, feedback-controlled manner, and express biological drugs against interleukin-1 (IL-1) or tumor necrosis factor A (TNF-A) [ 69 ]. Inflammatory cytokines are the most important compounds involved in the pathogenesis of OA [ 70 ], and they imbalance the homeostasis of the joint tissue by promoting catabolic and destructive processes [ 71 ].…”
Section: Engineering Mscs Behavior Through Materials-mediated Gene Delivery and Gene Editingmentioning
confidence: 99%
“…Similarly, the base sequences expressing IL-1Ra or soluble TNFR1 (sTNFR1) were inserted downstream of the promoter of gene CCL2 to construct a dynamic negative feedback circuit activated by IL-1 or TNF using CRISPR gene editing ( Figure 5(b) ) [ 70 ]. During the latter research, the iPSCs in combination with a 3D PCL woven scaffolds were engineered to form a stable cartilaginous implant to alleviate the inflammation in a RA model [ 71 ]. The union of tissue engineering and synthetic biology promises a wide range of potential therapeutic applications for treating chronic diseases such as OA and RA by producing specially designed stem cells that not only can differentiate into tissue-specific cell types but can also regulate the expression of transgene molecules in direct response to dynamically changing pathologic signals in vivo.…”
Section: Overcoming Clinical Challenges From Modulating a Regeneramentioning
confidence: 99%
“…B). These iPSCs were engineered to form implantable self‐regulating tissue constructs and have shown promising efficacy in early studies in a model of inflammatory arthritis …”
Section: Creating Self‐regulating “Smart” Cellsmentioning
confidence: 99%
“…These iPSCs were engineered to form implantable self-regulating tissue constructs and have shown promising efficacy in early studies in a model of inflammatory arthritis. 68 "Designer" stem cells have the potential to overcome challenges with long-term therapeutic delivery of biologic drugs as well as limitations involved in cell homing and engraftment. The development of selfregulating 67 or exogenously controlled 48 systems for transgene expression may allow for a new generation of stem cells that can not only be used to engineer tissue replacements but simultaneously may serve as an inducible and tunable depot for localized delivery of biologic drugs.…”
Section: Creating Self-regulating "Smart" Cellsmentioning
confidence: 99%